PROFESI AKUNTAN SYARIAH UNTUK MENDUKUNG PEREKONOMIAN SYARIAH - Riska Septiana Estutik; Amrie Firmansyah (Politeknik Negeri Jakarta, 2019)
ABSTRACT The development of the Islamic economy in Indonesia, which has begun to creep up, shows ashift in interest in public transactions that began to glance at the Islamic market. This paper aims toreview existing literature to provide the need for the sharia accountant profession to encourage thedevelopment of sharia economics from stakeholder theory. The result of the study suggests that thesharia accountant profession is needed to provide guarantees to stakeholders on the reliability ofinformation needed for decision making related to sharia financial transactions. Also, shariaaccountants are expected to become gatekeepers so that cases that have the potential to harmstakeholders do not occur. However, the availability of qualified human resources to meet the demandof sharia accountants is still limited, so it needs support from various parties such as the governmentand professional organizations such as the Indonesian Institute of Accountants to develop the shariaaccountant profession. Keywords: sharia accountant profession, stakeholders theory ABSTRAKPerkembangan ekonomi syariah di Indonesia yang mulai merangkak naik, menunjukkanpergeseran minat transaksi masyarakat yang mulai melirik pasar syariah. Makalah ini melakukantelaah atas pustaka yang telah ada untuk memberikan gambaran perlunya profesi akuntan syariahdalam mendorong perkembangan ekonomi syariah dilihat dari sudut pandang stakeholders theory.Dari hasil telaah, diketahui bahwa profesi akuntan syariah sangat dibutuhkan untuk memberikanjaminan kepada stakeholders atas keandalan informasi yang diperlukan untuk pengambilankeputusan terkait transaksi keuangan syariah. Selain itu, akuntan syariah juga diharapkan dapatmenjadi gatekeeper agar kasus-kasus yang berpotensi merugikan stakeholders tidak terjadi. Namundemikian, ketersediaan sumber daya manusia yang mumpuni untuk memenuhi permintaan akuntansyariah masih terbatas sehingga perlu dukungan dari berbagai pihak seperti pemerintah maupunorganisasi profesi seperti Ikatan Akuntan Indonesia untuk pengembangan profesi akuntan syariah. Kata kunci: profesi akuntan syariah, stakeholders theory